Peristaltic flow of Powell-Eyring fluid in curved channel with heat transfer: A useful application in biomedicine. Issue 135 (October 2016) - Hina, S.; Mustafa, M.; Hayat, T.; Alsaedi, A.
Highlights: Peristaltic (blood) flow in curved channel having complaint walls is considered. Problem formulation is based on constitutive equations of well known Powell-Eyring fluid. Velocity slip and temperature jump conditions are employed. Symmetry in the velocity and temperature profiles are not preserved in curved channel. Size and shape of trapped boluses in upper and lower halves are different. Abstract: Background and objective: In this work, we explore the heat transfer characteristics in the peristaltic transport of Powell-Eyring fluid inside a curved channel with complaint walls. The study has motivation toward the understanding of blood flow in microcirculatory system. Method: Formulation is developed in the existence of velocity slip and temperature jump conditions. Perturbation approach has been utilized to present series expressions of axial velocity and temperature distributions. Streamlines are prepared to analyze the interesting phenomenon of trapping. Moreover, the plots of heat transfer coefficient for a broad range of embedded parameters are presented and discussed. Results: The results indicate that slip effects substantially influence the velocity and temperature distributions. Axial flow accelerates when slip parameter is incremented. Temperature rises and wall heat flux grows when viscous dissipation effect is strengthened. In contrast to the planar channels, here velocity and temperature functions do not exhibit symmetry with respect to the central line. In addition, bolus size and its shape are different in upper and lower portions of the channel. Conclusions: Heat transfer coefficient enlarges when the curvature effects are reduced. The behaviors of wall tension and wall mass parameters on the profiles are qualitatively similar.